Two-period discount pricing strategies for an e-commerce platform with strategic consumers. (September 2020) - Li, Chunfa; Chu, Mingsen; Zhou, Chi; Zhao, Lianxia
Highlights: We study different discount pricing strategies of online coupons with strategic consumers. Two-period model is established to study three online coupon strategies. The large online coupon discount will reduce the total demand under the instant strategy. Fraction of strategic consumers and consumer penitence degree affect platform's strategy choices. The existence of strategic consumers will increase the product prices for two-period. Abstract: Flourishing online retail models have prompted platforms to design different discount pricing strategies of online coupons for strategic consumer behavior. To this end, we establish two-period models to study a platform's discount pricing strategies with strategic consumers. The framework of this study includes three different online coupon redemption strategies: The first is an instant strategy, in which the platform recommends one short-term coupon in period 1, and consumers can only redeem the coupon in period 1; the second is a continuous strategy, in which the platform recommends one long-term coupon in period 1, but consumers can only redeem the coupon in period 2; and the third is a hybrid strategy, in which the platform recommends two coupons including one short-term coupon and one long-term coupon in period 1, and consumers can redeem one coupon in each period. The optimal discount pricing and online coupon strategy choices of the e-commerce platform are analyzed in light of this framework. The main findings are as follows. First, if the online coupon discount in period 1 is relatively large, the platform should give priority to the instant strategy while the continuous strategy is the suboptimal choice. When the degree of consumer patience and the fraction of strategic consumers are within a reasonable interval, the hybrid strategy and the continuous strategy can replace each other. Second, it is not always better to recommend two online coupons (one short-term and one long-term) simultaneously than to recommend one single online coupon (one short-term or one long-term) each time. Furthermore, we examine how the fraction of strategic consumers and the degree of consumer penitence interact with the platform's strategy choice. Third, the existence of strategic consumers will force the platform to increase product prices for two periods.